2001
DOI: 10.1016/s0735-1097(01)01135-4
|View full text |Cite
|
Sign up to set email alerts
|

Extensive development of vulnerable plaques as a pan-coronary process in patients with myocardial infarction: an angioscopic study

Abstract: In patients with MI, all three major coronary arteries are widely diseased and have multiple yellow though nondisrupted plaques. Acute MI may represent the pan-coronary process of vulnerable plaque development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
175
1
5

Year Published

2003
2003
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 355 publications
(193 citation statements)
references
References 18 publications
12
175
1
5
Order By: Relevance
“…There was no significant difference of smoking status between low HDL-C group and normal HDL-C group (p=0.546). This result was correlated with the study of Asakura et al 26 that 56.0% of their patients were smoker. This result was also correlated with the study of Kabir et al 27 that 60.0% of their patients of CAD were smoker.…”
Section: Materials and Methodsupporting
confidence: 90%
See 1 more Smart Citation
“…There was no significant difference of smoking status between low HDL-C group and normal HDL-C group (p=0.546). This result was correlated with the study of Asakura et al 26 that 56.0% of their patients were smoker. This result was also correlated with the study of Kabir et al 27 that 60.0% of their patients of CAD were smoker.…”
Section: Materials and Methodsupporting
confidence: 90%
“…This result was also supported by Okamatsu et al 30 that 54.0% of their patients were hypertensive. In this regards Asakura et al 26 found 60.0% of their patient were hypertensive.…”
Section: Materials and Methodmentioning
confidence: 83%
“…This could contribute to the explanation of the pan-coronary syndrome. 1,2 It has been suggested that increased endothelial apoptosis leads to atheroma denudation and subsequent coronary thrombosis. [5][6][7][8][9]24 Endothelial apoptosis could also increase susceptibility toward coronary thrombosis through the release of apoptotic cell debris into the blood stream, which is known to directly activate coagulation cascade.…”
Section: Original Findingsmentioning
confidence: 99%
“…1,2 The finding that patients immediately after AMI are at increased risk for additional acute coronary events caused by previously nonoffending plaques 3,4 has generated the hypothesis that circulating factors induce vascular smooth muscle and endothelial damages that in turn could be responsible for plaque activation. Several studies have demonstrated the presence of apoptosis in atherosclerotic plaques that could lead to plaque denudation and subsequent transition to vulnerability.…”
mentioning
confidence: 99%
“…Therefore, our result suggests that a low plasma EPA/AA ratio may provide further information regarding the coronary vulnerability of patients with sAP, since the plaque instability represent a 'pan-coronary' process, but not a local vascular accident (13). Indeed, subanalysis of JELIS (3) has shown that adding purified EPA to statin has beneficial effects on the secondary prevention of CAD, and that a low blood EPA/AA ratio is an independent predictor for sudden cardiac death or fatal/nonfatal myocardial infarction in this population (6).…”
Section: Discussionmentioning
confidence: 79%